(untitled) (Historia, 2021)
Out of the cover of Charles van Onselen's newest magnum opus - a striking cover, the colour of dried blood and darkness, glossy embossed flies hovering - the man stares with eyes that gleam with an unnatural glassiness. This photographed figure reminds me of Charles Dickens' portrayal of Blandois, an ugly insinuating presence in his novel Little Dorrit, "with his moustache going up and his nose coming down in that most evil of smiles, and with his surface eyes looking as if they belonged to his dyed hair, and had had their natural power of reflecting light stopped" by some unnerving natural process. However, Dickens insists, Nature "is never to blame in any such instance".